Analisis Implementasi Stock Opname Internal pada Manajemen Pergudangan Perusahaan (Studi Kasus: PT. Granitoguna Building Ceramics) - Marco Veris Jeremi; Dene Herwanto (Jurnal Serambi Engineering, 2021)
To maintain company quality, the warehousing system must also be maintained so that stored items are controlled and easily accessible, both physically and in a system, so that it is easier for employees to run the work wheels optimally and efficiently. One thing that can be done to control the stock of goods is stocktaking. Stocktaking is an activity  of inspecting and  recovering the assets of the enterprise as a whole to maintain the quality of the collection and maximize the development activities of the company’s collection. This research was conducted by observing the application of stocktaking in GHPA01 and GHPA02 warehouse PT. Granitoguna Building Ceramics for one month. The purpose of this study was to determine the effect of stock accuracy, both physically and  in GHPA01 and GHPA02. The results showed that there was an increase in the level of accuracy of the quantity and shading accuracy  before and after the stocktaking was done in the warehouse  producing  results. The internal stocktaking process has a major effect on the accuracy of the stock, both physically and systemically, so a structured and planned inventory is needed to balance the accuracy of the system and physically can be balanced.